THE FUNCTION AND MEANING OF WORK AND THE JOB: MORSE AND WEISS (1955) REVISITED - Vecchio, Robert P. (Academy of Management Journal, 1980)
The article presents the results of a study that revisits an earlier study pertaining to the function and meaning of work. The original study asserted that the function of work as a purely an economic function or just a way to earning a living is incorrect. According to the original study, work also serves as a vehicle to avoid boredom, achieve personal fulfillment and to provide a forum for social contact. While the new study finds that the majority of workers still work for the aforementioned reasons, the proportion of people who work solely for economic purposes is greater.